Lithium metal material, method for controlling orientation of crystal face of lithium metal, pole piece and battery

By performing multiple stretching treatments and polymer film coating on the metal lithium foil at a dew point below -40°C, the (110) crystal plane orientation of the lithium metal battery is controlled, and the risk of internal short circuits and traditional processes of lithium metal batteries are solved. The problem of difficulty in achieving industrialization improves the cycle life and production efficiency of the battery.

CN119133423APending Publication Date: 2024-12-13ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411199578.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Lithium metal batteries are prone to form one-dimensional dendrites under high current conditions, resulting in the risk of internal short circuits. In addition, traditional roller pressing methods have problems of hardening and alloying, making it difficult to achieve industrialization.

Method used

By performing multiple stretching treatments on the metal lithium foil at a dew point below -40°C, the (110) crystal surface is exposed, and combined with polymer film coating and disposable rolling treatment, the crystal surface orientation is controlled to improve ( 110) The intensity and exposure of the crystal surface.

Benefits of technology

It effectively reduces the internal short circuit risk of lithium metal batteries under large current and long cycle conditions, simplifies the process flow, avoids hardening of rolling materials, and realizes industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005017508400000081
    Figure BDA0005017508400000081
  • Figure BDA0005017508400000091
    Figure BDA0005017508400000091
Patent Text Reader

Abstract

The invention discloses a metal lithium material, a method for controlling orientation of a metal lithium crystal face, a pole piece and a battery. The surface of the metal lithium material is provided with a (110) crystal face, a (211) crystal face and a (200) crystal face; the ratio of the characteristic peak intensity of the (110) crystal face to the characteristic peak intensity of the (211) crystal face is greater than or equal to 3, and the ratio of the characteristic peak intensity of the (110) crystal face to the characteristic peak intensity of the (200) crystal face is greater than or equal to 3. The surface (110) crystal face of the metal lithium material is high in strength, has a high-exposure (110) crystal face and can be applied to a lithium metal battery, and because the diffusion energy barrier of lithium ions on the surface of the lithium (110) crystal face is relatively low, a high-dimensional structure instead of a one-dimensional dendritic crystal tends to be generated, so that the metal lithium material can be applied to the lithium metal battery. And after the metal lithium material is applied to the lithium metal battery, the risk of internal short circuit under the condition of large current and long circulation can be effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery pole piece materials, and in particular to a metallic lithium material, a method for controlling the crystal plane orientation of metallic lithium, a pole piece and a battery. Background Art

[0002] With the rapid development of science and technology and the widespread popularity of electronic devices, electric vehicles and other fields, people's demand for high-efficiency and high-energy-density batteries is growing. Traditional battery technology can no longer meet this growing demand, so it is necessary to develop new battery technology to meet the urgent needs of the market.

[0003] Among these new batteries, lithium metal batteries have attracted much attention because the lithium metal battery system has a higher energy density. The gram capacity of lithium metal is as high as 3860mAh / g (11 times higher than graphite), and the redox potential is as low as -3.04V compared with the standard hydrogen electrode (which means the discharge voltage platform is higher). According to calculations, if the graphite negative electrode in the battery is replaced with lithium metal, the volume ED gain of the battery will increase by up to 62%, and the weight ED gain can increase by up to 45%, which means that at the same volume and weight, the battery can store more energy, and electric vehicles, mobile phones and other devices will have a longer battery life.

[0004] However, lithium metal batteries face many challenges in practical applications, such as impractical rate performance, unsafe cycling conditions and limited cycle life. In order to solve these problems, the scientific community is committed to developing new lithium metal matrices starting from lithium metal materials.

[0005] Studies have shown that the surface diffusion barrier of lithium ions on the lithium (110) crystal plane is low, and it tends to generate high-dimensional structures rather than one-dimensional dendrites. However, existing commercial lithium foils usually exhibit three types of crystal planes on the surface at the same time: (110), (200) and (211). Among them, the (110) crystal plane has low strength and a large surface diffusion barrier, which makes it easy to form one-dimensional dendrites under high current conditions. After long cycles, the disordered growth of dendrites can easily puncture the diaphragm, causing a short circuit between the positive and negative electrodes, posing a safety risk. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a metallic lithium material, a method for controlling the crystal plane orientation of metallic lithium, a pole piece and a battery.

[0007] In a first aspect of the present invention, a metallic lithium material is proposed, wherein the surface of the metallic lithium material has a (110) crystal plane, a (211) crystal plane and a (200) crystal plane; the ratio of the characteristic peak intensity of the (110) crystal plane to the characteristic peak intensity of the (211) crystal plane is greater than or equal to 3, and the ratio of the characteristic peak intensity of the (110) crystal plane to the characteristic peak intensity of the (200) crystal plane is greater than or equal to 3.

[0008] The metallic lithium material according to the embodiment of the present invention has at least the following beneficial effects: the surface (110) crystal plane strength of the metallic lithium material is high, and the (110) crystal plane is highly exposed, so the metallic lithium material can be applied to lithium metal batteries. Since the surface diffusion energy barrier of lithium ions on the lithium (110) crystal plane is low, a high-dimensional structure rather than a one-dimensional dendrite is tended to be generated. Therefore, the metallic lithium material can effectively reduce the risk of internal short circuit under high current and long cycle conditions after being applied to lithium metal batteries.

[0009] In some embodiments of the present invention, the thickness of the metallic lithium material is 8 μm to 350 μm; further, the thickness of the metallic lithium material may be 10 μm to 300 μm, 50 μm to 250 μm, 100 μm to 200 μm, 60 μm to 220 μm, 50 μm to 150 μm, 20 μm to 80 μm, 50 μm to 100 μm, 150 μm to 300 μm, etc.

[0010] In some embodiments of the present invention, the density of the lithium metal material is 0.534 g / cm 3 ~0.545g / cm 3 .

[0011] The traditional method of exposing the (110) crystal plane is usually achieved by accumulating the number of rolling-bonding times (more than 8 times), specifically by multiple rolling to expose the (110) crystal plane. This method has practical disadvantages: since the size of lithium grains decreases with the increase in the number of rolling-bonding times, smaller grains will lead to a decrease in the space for atomic dislocation, so the lithium metal foil will gradually harden during the rolling process, and the hardening of the rolled material will further seriously affect the service life of the roller; in addition, in industrial applications, lithium metal cannot directly contact the roller, and lithium metal and the roller material will alloy. Therefore, in the general lithium rolling process, PET is required as a film to isolate the contact between lithium metal and the roller material, which makes rolling-bonding difficult to achieve industrialization.

[0012] In this regard, the second aspect of the present invention provides a method for controlling the crystal plane orientation of metallic lithium, comprising: stretching metallic lithium foil at a dew point below -40°C.

[0013] The method for controlling the crystal plane orientation of metal lithium according to the embodiment of the present invention has at least the following beneficial effects: the method can promote the metal lithium foil to expose the (110) crystal plane orientation by stretching the metal lithium foil. Specifically, the metal lithium foil is a polycrystalline material composed of many domains. Commercial lithium foil can usually show three types of characteristic peaks under XRD detection, which belong to the three lithium crystal planes (110), (200) and (211). When the metal lithium foil is subjected to a specific tensile external force, the material itself will undergo grain rotation, grain boundary sliding and lattice dislocation in order to adapt to the direction of the external stress, that is, crystal plane deformation, and crystal plane deformation tends to occur along the crystal plane with dense atomic arrangement, thereby causing these planes to align in a specific direction, thereby promoting the exposure of more (110) crystal planes. The above method can facilitate the realization of the (110) crystal plane orientation of metal lithium through stretching treatment. Compared with the method of exposing the (110) crystal plane of metal lithium by rolling-bonding several times, the operation is simple, which is conducive to industrialization, and can avoid the problem of hardening of rolled materials due to multiple rolling.

[0014] Among them, the dew point is the dew point temperature, which refers to the temperature at which the relative humidity in the air is saturated, and can also be understood as the temperature at which water vapor and water reach a state of equilibrium. The lower the dew point temperature, the drier the air. Since metal lithium foil is highly active, the presence of moisture will affect the performance and quality of the product during the stretching process of metal lithium foil. Specifically, lithium metal will undergo an irreversible chemical reaction under conditions where the dew point temperature is too high (such as above -40°C). The reaction equation is: 2Li+2H2O=2LiOH+H2. The reaction is violent and releases a lot of heat, and hydrogen is a flammable gas that can easily cause uncontrolled combustion reactions. In addition, the lithium in LiOH has no reaction activity and is a "dead lithium" component after assembling the battery cell. It not only affects the insertion and extraction of lithium ions during the deposition process, but also occupies a certain volume and weight, reducing the energy density of the battery cell, and is an undesirable component. Therefore, lithium metal should not be exposed to the air under high dew point conditions, and the dew point needs to be monitored and strictly controlled to be below -40°C during the process of controlling the orientation of the metal lithium crystal plane (including stretching).

[0015] In some embodiments of the present invention, the stretching process includes at least two stretchings, and each stretching is performed along the same direction of the metal lithium foil. The number of stretchings during the stretching process can be specifically 3 times, 5 times, 6 times, 8 times, 10 times, 11 times, etc. As mentioned above, by applying a tensile force to the metal lithium foil, the material tends to deform along the crystal planes where atoms are closely arranged in order to adapt to the direction of the external stress, thereby causing these planes to align in a specific direction, exposing the metal lithium (110) crystal plane, and as the number of stretchings in the same direction increases, the alignment degree continues to increase, which can be conducive to the formation of a highly exposed (110) crystal plane, and even tends to form a metal lithium material containing a single (110) crystal plane.

[0016] In some embodiments of the present invention, during the stretching process, after each stretching is completed, the stretched metal lithium foil is first folded in half before the next stretching is performed. The folding can be specifically symmetrically folded along the midline of the wide surface of the stretched metal lithium foil. Stretching is a key process for exposing the (110) crystal plane. By stretching the metal lithium foil multiple times, the peak intensity of the lithium (110) crystal plane can be significantly enhanced. However, since the thickness of the metal lithium foil will become thinner as the stretching process proceeds, by adding a folding process between two adjacent stretching processes, the product can be controlled to a certain thickness to ensure the strength of the stretched material, thereby preventing the material from breaking due to stretching and improving the stability and reliability of the stretching process.

[0017] In some embodiments of the present invention, during the stretching process, after the first stretching is completed, the folding and stretching are repeated 5 to 10 times, that is, during the stretching process, the number of stretching times can be controlled at 6 to 11 times. Increasing the number of stretching times can increase the crystal plane alignment, which is conducive to the formation of a metallic lithium material with a single (110) crystal plane.

[0018] In some embodiments of the present invention, during the stretching process, the stretching force applied each time is 2N / cm 2 ~20N / cm 2 ; and / or, the elongation of each stretching is controlled at 50% to 80%.

[0019] The magnitude of the stretching force during the stretching process determines the stretching speed. The transformation of the crystal plane of a polycrystalline material under external force requires strain time. If the stretching speed is too fast, an orderly texture evolution of the metallic lithium cannot be formed, and if the stretching force is too small, the metallic lithium will not be extended. By controlling the stretching force applied during the stretching process to 2N / cm 2 ~20N / cm 2 , the stretching speed can be effectively controlled to make the metal lithium undergo crystal plane transformation to form an orderly texture evolution. Furthermore, the stretching force applied during the stretching process can be 5N / cm 2 ~20N / cm 2 , 5N / cm 2 ~15N / cm 2 , 6N / cm 2 ~18N / cm 2 , 8N / cm 2 ~16N / cm 2 , 10N / cm 2 ~15N / cm 2 , 6N / cm 2 ~12N / cm 2 Alternatively, the stretching force applied during the stretching process may be 3N / cm 2 , 5N / cm 2 , 7N / cm2 , 9N / cm 2 , 10N / cm 2 , 12N / cm 2 , 14N / cm 2 , 15N / cm 2 , 17N / cm 2 , 19N / cm 2 , 20N / cm 2 wait.

[0020] The elongation of the stretching treatment mainly affects the evolution effect of the (110) crystal plane. If the elongation is too large, it may cause the metal lithium to break. If it is too small, the shortest distance for the (110) crystal plane to evolve is not reached. Then, by controlling the elongation of the stretching treatment within the range of 50% to 80%, the metal lithium can be guaranteed to effectively evolve the (110) crystal plane. Further, the elongation of the stretching treatment can be controlled within the range of 55% to 75%, 55% to 65%, 60% to 80%, 60% to 70%, 65% to 75%, or the elongation of the stretching treatment can be controlled to 50%, 52%, 58%, 60%, 63%, 65%, 68%, 70%, 72%, 75%, 77%, 80%, etc.

[0021] In addition, the stretching process can be performed by fixing the opposite ends of the metal lithium foil, specifically, stretching along the length direction of the metal lithium foil, or stretching along the width direction of the metal lithium foil. When the stretching process includes multiple stretching, each stretching needs to be controlled to be performed along the same direction of the metal lithium foil.

[0022] In some embodiments of the present invention, the density of the metal lithium foil changes by 0-2% before and after the stretching treatment. The stretching treatment is essentially to apply an external stress to the metal lithium foil, which will cause the grain size to decrease. Smaller grains will lead to a reduction in the space where atomic dislocation occurs. From the perspective of physical and chemical properties, the material becomes harder and the density increases. The small grains have a denser lithium layer during initial deposition and the volume ED increases.

[0023] In some embodiments of the present invention, the thickness of the metal lithium foil is 20μm to 500μm. Further, the thickness of the metal lithium foil may be 50μm to 500μm, 50μm to 450μm, 80μm to 400μm, 100μm to 450μm, 150μm to 400μm, 150μm to 350μm, 200μm to 500μm, 250μm to 450μm, 250μm to 350μm, 300μm to 500μm, 300μm to 400μm, etc.

[0024] In some embodiments of the present invention, after the stretching treatment is completed, the method further includes: coating the stretched lithium foil with a polymer film, and then performing a roll pressing treatment. Since the metal lithium foil can be exposed to the (110) crystal plane orientation by stretching the metal lithium foil before the roll pressing treatment, only one roll pressing treatment is required for shaping after the stretching treatment is completed. Compared with the conventional method of exposing the metal lithium (110) crystal plane, which requires several roll pressing-bonding processes, and the polymer film is required to isolate the roller before each roll pressing, this method is simple to operate, can greatly reduce the input of materials and manpower, is more conducive to industrialization, and can avoid the problem that the traditional method of using multiple roll pressings easily causes the roll pressing material to harden and affects the service life of the roller.

[0025] In some embodiments of the present invention, the thickness change of the metal lithium foil before and after the rolling treatment is controlled at 30% to 50%; and / or, after the stretching treatment is completed, the stretched metal lithium foil is first folded in half, and then the folded metal lithium foil is coated with a polymer film, and then the rolling treatment is performed.

[0026] Among them, since the rolling process will produce stress on the lithium metal strip, resulting in a smaller crystal size and crystal plane transformation, therefore, in the product molding process, the thickness change during rolling should be reduced so that the product can maintain as many (110) crystal planes as possible, and too small a thickness change cannot form a smooth lithium metal surface. Therefore, by controlling the thickness change of the metal lithium foil before and after the rolling process to 30% to 50%, it can be ensured that the molding obtains a smooth surface of the lithium metal material, while the product lithium metal material maintains more (110) crystal planes. The thickness change rate of the metal lithium foil before and after the rolling process can be further controlled to 32% to 48%, 35% to 45%, 38% to 42%, 35% to 40%, 40% to 45%, 40% to 50%, or the thickness change rate of the metal lithium foil before and after the rolling process can be controlled to 30%, 33%, 35%, 37%, 40%, 43%, 45%, 47%, 48%, 50%, etc.

[0027] After the stretching process is completed, the stretched lithium metal foil can be folded in half to control the material to a certain thickness, and then the folded lithium metal foil is coated with a polymer film and then rolled.

[0028] Before the rolling process, the folded metal lithium foil is first coated with a polymer film to isolate the metal lithium foil from contact with the roller during the rolling process, thereby avoiding direct contact between the metal lithium foil and the roller material to cause alloying. In some embodiments of the present invention, in step S3, the polymer film is selected from polyethylene terephthalate (PET) film or polyimide film.

[0029] In some embodiments of the present invention, the method for controlling the orientation of the metallic lithium crystal plane specifically comprises the following steps:

[0030] S1. Under the condition of dew point lower than -40℃, the metal lithium foil is stretched; wherein the stretching process includes 6 to 11 stretchings, and after each stretching, the stretched metal lithium foil is folded in half before the next stretching, that is, after the first stretching, the folding and stretching are repeated 5 to 10 times; the stretching force applied for each stretching is 2N / cm 2 ~20N / cm 2 , the elongation of each stretch is controlled at 50% to 80%;

[0031] S2, folding the stretched lithium metal foil in half, and then coating the folded lithium metal foil with a polymer film, and then performing a roller pressing process; the thickness change rate of the lithium metal foil before and after the roller pressing process is controlled to be 30% to 50%.

[0032] The metallic lithium material obtained by the above method of controlling the crystal plane orientation of metallic lithium has a (110) crystal plane, a (211) crystal plane and a (200) crystal plane on its surface; the ratio of the characteristic peak intensity of the (110) crystal plane to the characteristic peak intensity of the (211) crystal plane is greater than or equal to 3, and the ratio of the characteristic peak intensity of the (110) crystal plane to the characteristic peak intensity of the (200) crystal plane is greater than or equal to 3, and has a highly exposed (110) crystal plane.

[0033] In a third aspect of the present invention, a pole piece is provided, wherein the pole piece is made of any of the aforementioned metal lithium materials and can be obtained by dividing the aforementioned metal lithium material.

[0034] In a fourth aspect of the present invention, a battery is provided, the battery comprising a positive electrode sheet, a negative electrode sheet and a separator, the separator is sandwiched between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet and / or the negative electrode sheet adopts any of the aforementioned electrode sheets. Since the battery adopts any of the aforementioned electrode sheets, the risk of internal short circuit under high current and long cycle conditions can be effectively reduced. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0036] Example 1

[0037] A method for controlling the crystal plane orientation of metallic lithium, the method comprising the following steps:

[0038] S1. Stretching the metal lithium foil in an environment where the dew point is lower than -40°C;

[0039] Specifically, in an environment with a dew point below -40°C, the metal lithium foil is fixed at both ends and a tensile machine is used to apply 10N / cm 2 The metal lithium foil is stretched with a tensile force of 50%, and the fixing clamp is released when the elongation is 50%, and the metal lithium foil is folded in half, and then the stretching operation is repeated, and then the folding and stretching operations are repeated; specifically, after the first stretching is completed, the folding and stretching are repeated 5 times, and each stretching is stretched in the same direction of the metal lithium foil; a high-intensity (110) crystal plane signal is detected on the surface of the metal lithium foil after the stretching treatment.

[0040] S2, folding the metal lithium foil after the stretching treatment in step S1 in half, and then coating the lithium metal foil with a polymer film, and then rolling the lithium metal foil, wherein the thickness of the metal lithium foil is reduced by 50% after the rolling treatment, to obtain a lithium metal material with uniform thickness and smooth surface.

[0041] Example 2

[0042] A method for controlling the crystal orientation of lithium metal, the difference between this method and embodiment 1 is that: in step S1, during the stretching process, the stretching force applied by the stretching machine is increased from 10N / cm 2 Adjustment 20N / cm 2 The other operations are the same as those in Example 1 to produce a lithium metal material with uniform thickness and smooth surface.

[0043] Example 3

[0044] A method for controlling the crystal plane orientation of metallic lithium, the difference between this method and Example 1 is that: in step S1, during the stretching process, the elongation of each stretching is adjusted from 50% to 80%, and other operations are the same as in Example 1, to produce a lithium metal material with uniform thickness and smooth surface.

[0045] Example 4

[0046] A method for controlling the crystal plane orientation of metallic lithium, the method differs from Example 1 in that: in step S1, in the stretching process, after completing the first stretching, the number of repetitions of folding and stretching is adjusted from 5 times to 10 times, and other operations are the same as in Example 1, to produce a lithium metal material with uniform thickness and smooth surface.

[0047] Example 5

[0048] A method for controlling the crystal plane orientation of metallic lithium, the method differs from Example 1 in that: in step S2, the rolling process is controlled so that the thickness reduction rate of the metallic lithium foil after the rolling process is adjusted from 50% to 30%, and other operations are the same as Example 1, so as to produce a lithium metal material with uniform thickness and smooth surface.

[0049] Example 6

[0050] A method for controlling the crystal orientation of lithium metal, the difference between this method and embodiment 1 is that: in step S1, during the stretching process, the stretching force applied by the stretching machine is increased from 10N / cm 2 Adjustment 30N / cm 2 , other operations are the same as those in Example 1.

[0051] Example 7

[0052] A method for controlling the crystal plane orientation of metallic lithium, the difference between this method and Example 1 is that: in step S1, during the stretching process, the elongation of each stretching is adjusted from 50% to 30%, and other operations are the same as Example 1.

[0053] Example 8

[0054] A method for controlling the crystal plane orientation of metallic lithium, the difference between this method and Example 1 is that: in step S1, in the stretching process, after completing the first stretching, the number of repetitions of folding and stretching is adjusted from 5 times to 4 times, and other operations are the same as Example 1.

[0055] Example 9

[0056] A method for controlling the crystal plane orientation of metallic lithium, the difference between this method and Example 1 is that: in step S2, the rolling process is controlled so that the thickness reduction rate of the metallic lithium foil after the rolling process is adjusted from 50% to 60%, and other operations are the same as Example 1.

[0057] Comparative Example 1

[0058] The original metal lithium foil without any treatment in Example 1 is used as Comparative Example 1.

[0059] Comparative Example 2

[0060] The difference between this comparative example and Example 1 is that in this comparative example, the process of step S1 in Example 1 is not performed, but the original metal lithium foil is directly folded in half according to the operation of step S2 in Example 1, and then the lithium metal foil is coated with a polymer film, and then the lithium metal foil is roll-pressed. After the rolling process, the thickness of the metal lithium foil is reduced by 50%, and the product lithium metal material is obtained.

[0061] Performance Testing

[0062] 1. Cut the metal lithium material samples obtained in each embodiment and comparative example into small square pieces of 1 cm*1 cm, and use XRD to detect the sample surface, with a scanning angle of 10-80° and a scanning speed of 2° / min; let the characteristic peak intensity of the (110) crystal plane be x(110), the characteristic peak intensity of the (200) crystal plane be y(200), and the characteristic peak intensity of the (211) crystal plane be z(211), and examine the characteristic peak intensity ratio of the (110) crystal plane to the (200) crystal plane and the (211) crystal plane to determine whether the sample achieves the expected effect. Specifically, when x(110) / z(211)≥3 and x(110) / y(200)≥3 are satisfied at the same time, it can be considered that the obtained sample achieves the expected effect. The results obtained by the above method are shown in Table 1.

[0063] 2. Cut the metal foil materials obtained in each embodiment and comparative example into 16 mm small discs, and assemble 2032 symmetrical batteries with two identical small discs, wherein the electrolyte formula is 1M LiPF6 ethylene carbonate (EC) / ethyl methyl carbonate (EMC) electrolyte, EC:EMC=3:7, and the diaphragm is a 14 μm thick PE diaphragm. Take 5 symmetrical batteries each, and set the current density to 1 mAh / cm 2 , set the single charge surface capacity to 1mAh / cm 2 , charge and discharge cycles were carried out at room temperature until the polarization voltage was greater than 0.2V, and the cycle life of each example was compared.

[0064] The test steps are as follows:

[0065] a. Leave for 5 minutes;

[0066] b. 1 mAh / cm 2 The current is constant current charged for 1h;

[0067] c. Leave for 5 minutes;

[0068] d. 1 mAh / cm 2 The current is discharged at a constant current for 1h;

[0069] e. Repeat 1-4 until the polarization voltage is greater than 0.5V;

[0070] f. End.

[0071] The cycle life of the symmetrical batteries made and assembled using the metal lithium materials of each embodiment and comparative example measured by the above method is shown in Table 1 below.

[0072] Table 1 Condition control and product performance test data of each embodiment and comparative example

[0073]

[0074]

[0075] As shown in Table 1 above, compared with Comparative Example 1, the metal lithium foil in each embodiment is stretched, and the (110) crystal plane strength in the product metal lithium material is higher, exposing more (110) crystal planes. Therefore, the method of controlling the orientation of the metal lithium crystal plane of the present invention can cause the metal lithium foil to expose the (110) crystal plane orientation by stretching the metal lithium foil. Compared with the method of exposing the metal lithium (110) crystal plane by rolling-bonding several times, the operation is simple, which is conducive to industrialization, and can avoid the problem that multiple rolling in the conventional method easily leads to hardening of the rolled material.

[0076] It can be seen from the experimental results of Comparative Example 2 that when the metal lithium foil is directly subjected to roller pressing, a large number of (200) crystal planes exist on the surface of the lithium foil, and the expected effect cannot be achieved.

[0077] In addition, by comparing the various embodiments, it can be seen that in the above method of controlling the crystal plane orientation of metallic lithium, the stretching force in the stretching process, the elongation of each stretching, the number of repeated folding-stretching, and the thickness change rate of the metallic lithium foil before and after rolling in the rolling process will affect the (110) crystal plane strength of the product metallic lithium material, and thus affect the cycle life of the battery.

[0078] Specifically, by comparing Examples 1, 2, and 6 and their performance test results, it can be seen that the stretching forces during the stretching process of Examples 1 and 2 are 10 N / cm 2 , 20N / cm 2 , the ratios of the characteristic peak intensity of the (110) crystal plane on the product metal lithium material to the characteristic peak intensity of the (211) crystal plane and the characteristic peak intensity of the (200) crystal plane are greater than 3, respectively, and the battery cycle life is high; compared with Examples 1 and 2, the tensile force in Example 6 is larger, and the ratio of the characteristic peak intensity of the (110) crystal plane on the product metal lithium material to the characteristic peak intensity of the (200) crystal plane is greater than 3, but the ratio of the characteristic peak intensity of the (110) crystal plane to the characteristic peak intensity of the (211) crystal plane is less than 3, and the battery cycle life is significantly lower than that of Examples 1 and 2. This is because the magnitude of the tensile force affects the tensile speed. It takes strain time for the polycrystalline material to undergo crystal plane transformation under external force. If the tensile speed is too fast, an orderly lithium metal texture evolution cannot be formed, and the (110) crystal plane cannot be effectively exposed; and if the tensile force is too small, the lithium metal will not be extended. Therefore, it is possible to consider controlling the tensile force in the tensile process to 2N / cm 2 ~20N / cm 2 , in order to effectively control the stretching speed, so that the metallic lithium undergoes crystal plane transformation to form an orderly texture evolution, so as to effectively expose the (110) crystal plane.

[0079] By comparing Examples 1, 3, and 7, it can be seen that the elongation of each stretching process in Examples 1 and 3 is 50% and 80% respectively, and the ratio of the characteristic peak intensity of the (110) crystal plane on the product metal lithium material to the characteristic peak intensity of the (211) crystal plane and the characteristic peak intensity of the (200) crystal plane is greater than 3, and the battery cycle life is high; while compared with Examples 1 and 3, the elongation of the stretching in Example 7 is smaller, and the ratio of the characteristic peak intensity of the (110) crystal plane on the product metal lithium material to the characteristic peak intensity of the (211) crystal plane and the characteristic peak intensity of the (200) crystal plane is less than 3, and the battery cycle life is significantly lower than the battery life constructed using the metal lithium foil material of Examples 1 and 3. This is because the elongation of the stretching mainly affects the evolution effect of the (110) crystal plane. If the elongation of the stretching is too large, it may cause the lithium metal to break; and if the elongation of the stretching is too small, it may not reach the effective distance for the evolution of the (110) crystal plane, and effective crystal plane deformation cannot be achieved. Therefore, it is considered that the elongation of each stretching process can be controlled within a range of 50% to 80%.

[0080] By comparing Examples 1, 4, and 8, it can be seen that in the stretching process in Examples 1 and 4, after the first stretching is completed, the folding-stretching is repeated 5 times and 10 times respectively, and the ratios of the characteristic peak intensity of the (110) crystal plane on the product metal lithium material to the characteristic peak intensity of the (211) crystal plane and the characteristic peak intensity of the (200) crystal plane are greater than 3, respectively, and the battery cycle life is high; while compared with Examples 1 and 4, the folding-stretching is repeated less in Example 8, and the ratios of the characteristic peak intensity of the (110) crystal plane on the product metal lithium material to the characteristic peak intensity of the (211) crystal plane and the characteristic peak intensity of the (200) crystal plane are less than 3, and thus the battery cycle life is significantly lower than that of the battery constructed using the metal lithium foil material of Examples 1 and 4. This is because repeated stretching is the key process for exposing the (110) crystal plane. When lithium metal foil is subjected to a specific tensile external force, the material itself will undergo crystal plane deformation in order to adapt to the direction of the external stress. Crystal plane deformation tends to occur along crystal planes with dense atomic arrangement, causing these planes to align in a specific direction. As the number of stretching increases, the degree of alignment continues to increase, eventually forming lithium metal containing only a single (110) crystal plane. If the number of stretching is not enough, it is not conducive to the exposure orientation of the (110) crystal plane. Furthermore, by comparing Example 8 with Comparative Example 1, the cycle life of the symmetrical battery of Example 8 is inferior to that of Comparative Example 1. The reason is that: it is calculated that the peak intensity ratio of the (110): (211): (200) crystal planes of the metallic lithium material obtained in Example 8 is 2.3:1:1.64; while the peak intensity ratio of the (110): (211): (200) crystal planes of the metallic lithium foil of Comparative Example 1 is 1:1:10. That is to say, the untreated metallic lithium foil is mainly composed of the 200 crystal plane, while the peak intensities of the crystal planes of the lithium foil after four folding-stretching treatments are similar. The presence of multiple crystal planes on the surface of the lithium foil will make the lithium deposition behavior more complicated, and will not improve the cycle life. On the contrary, it may show a trend of deterioration.

[0081] In addition, by comparing Examples 1, 5, and 9, it can be seen that the thickness change rate before and after the rolling treatment in Examples 1 and 5 is 50% and 30% respectively, and the ratio of the characteristic peak intensity of the (110) crystal plane on the product metal lithium material to the characteristic peak intensity of the (211) crystal plane and the characteristic peak intensity of the (200) crystal plane is greater than 3, and the battery cycle life is high; while compared with Examples 1 and 5, the thickness change in Example 9 during the rolling process is too large, and the ratio of the characteristic peak intensity of the (110) crystal plane on the product metal lithium material to the characteristic peak intensity of the (211) crystal plane and the characteristic peak intensity of the (200) crystal plane is less than 3, and the battery cycle life is lower than the battery cycle life constructed using the metal lithium materials of Examples 1 and 5. This is because the final rolling process will also generate stress on the lithium metal strip, resulting in smaller crystal size and crystal plane transformation. Therefore, in the product molding process, the thickness change during rolling should be reduced so that the product can maintain as many (110) crystal planes as possible, and too small a thickness change cannot form a smooth lithium metal surface. Therefore, it can be considered that the thickness change of the metal lithium foil before and after the roll pressing process is controlled within 30% to 50%.

[0082] From the above, it can be seen that the exposure degree (or strength) of the (110) crystal plane significantly affects the cycle life of the battery. Specifically, when the ratio of the characteristic peak intensity of the (110) crystal plane to the characteristic peak intensity of the (211) crystal plane on the metal lithium material is greater than or equal to 3, and the ratio of the characteristic peak intensity of the (110) crystal plane to the characteristic peak intensity of the (200) crystal plane is greater than or equal to 3, the risk of internal short circuit of the lithium metal battery under high current and long cycle conditions can be effectively reduced, and the cycle life of the battery is significantly improved. Because the (211) and (200) crystal planes tend to generate one-dimensional whiskers, that is, lithium dendrites due to the existence of energy barriers, and the (110) crystal plane tends to deposit into a high-dimensional structure, and the surface is flat after deposition. During cycling, the growth of dendrites leading to internal short circuits in the battery is often a local behavior. The fewer (211) and (200) crystal planes, the lower the probability of growing dendrites and piercing the diaphragm.

[0083] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A metallic lithium material, characterized in that: The surface of the metallic lithium material has a (110) crystal plane, a (211) crystal plane and a (200) crystal plane; the ratio of the characteristic peak intensity of the (110) crystal plane to the characteristic peak intensity of the (211) crystal plane is greater than or equal to 3, and the ratio of the characteristic peak intensity of the (110) crystal plane to the characteristic peak intensity of the (200) crystal plane is greater than or equal to 3.

2. The metallic lithium material according to claim 1, characterized in that The thickness of the metallic lithium material is 8 μm to 350 μm; And / or, the density of the lithium metal material is 0.534 g / cm 3 ~0.545g / cm 3 .

3. A method for controlling the crystal plane orientation of metallic lithium, characterized in that: include: The metal lithium foil is stretched under the condition of dew point below -40℃.

4. The method for controlling the crystal plane orientation of metallic lithium according to claim 3, characterized in that: The stretching process includes at least two stretching steps, and each stretching step is performed along the same direction of the metal lithium foil.

5. The method for controlling the crystal plane orientation of metallic lithium according to claim 4, characterized in that: During the stretching process, after each stretching is completed, the stretched metal lithium foil is first folded in half before the next stretching is performed.

6. The method for controlling the crystal plane orientation of metallic lithium according to claim 5, characterized in that: During the stretching process, after the first stretching is completed, the folding and stretching are repeated 5 to 10 times.

7. The method for controlling the crystal plane orientation of metallic lithium according to claim 5, characterized in that: During the stretching process, the stretching force applied each time is 2N / cm 2 ~20N / cm 2 ; and / or, the elongation of each stretching is controlled at 50% to 80%.

8. The method for controlling the crystal plane orientation of metallic lithium according to claim 3, characterized in that: The thickness of the metal lithium foil is 20 μm to 500 μm.

9. The method for controlling the crystal plane orientation of metallic lithium according to any one of claims 3 to 8, characterized in that: After the stretching process is completed, the method further includes: coating the stretched metal lithium foil with a polymer film, and then performing a roll pressing process.

10. The method for controlling the crystal plane orientation of metallic lithium according to claim 9, characterized in that: The thickness change rate of the metal lithium foil before and after the rolling process is controlled to be 30% to 50%; and / or, After the stretching process is completed, the stretched metal lithium foil is first folded in half, and then the folded metal lithium foil is coated with a polymer film, and then a rolling process is performed.

11. A pole piece, characterized in that: The material of the pole piece is the metallic lithium material described in any one of claims 1 to 2 or the metallic lithium material obtained by the method for controlling the crystal plane orientation of metallic lithium described in any one of claims 3 to 10.

12. A battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is sandwiched between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet and / or the negative electrode sheet adopts the electrode sheet according to claim 11.